An ectopically expressed serum miRNA signature is prognostic, diagnostic, and biologically related to liver allograft rejection. Issue 1 (5th October 2016) - Shaked, Abraham; Chang, Bao‐Li; Barnes, Michael R.; Sayre, Peter; Li, Yun R.; Asare, Smita; DesMarais, Michele; Holmes, Michael V.; Guettouche, Toumy; Keating, Brendan J.
Abstract : The ability to noninvasively diagnose acute cellular rejection (ACR) with high specificity and sensitivity would significantly advance personalized liver transplant recipient care and management of immunosuppression. We performed microRNA (miRNA) profiling in 318 serum samples from 69 liver transplant recipients enrolled in the Immune Tolerance Network immunosuppression withdrawal (ITN030ST) and Clinical Trials in Organ Transplantation (CTOT‐03) studies. We quantified serum miRNA at clinically indicated and/or protocol biopsy events (n = 130). The trajectory of ACR diagnostic miRNAs during immunosuppression withdrawal were also evaluated in sera taken at predetermined intervals during immunosuppression minimization before and at clinically indicated liver biopsy (n = 119). Levels of 31 miRNAs were significantly associated with ACR diagnosis with two miRNAs differentiating ACR from non‐ACR (area under the receiver operating characteristic curve = 90%, 95% confidence interval = 82%‐96%) and predicted ACR events up to 40 days before biopsy‐proven rejection. The most differentially expressed miRNAs were low or absent in the blood of healthy individuals but highly expressed in liver tissue, indicating an ectopic origin from the liver allograft. Pathway analyses of rejection‐associated miRNAs and their target messenger RNAs (mRNAs) showed induction of proinflammatory and cell death‐related pathways. Integration of differentially expressed serum miRNA with concordant liver biopsy mRNA demonstrates interaction between molecules with a known role in transplant rejection. Conclusion: Distinct miRNA levels profiled from sera at the time of clinical allograft dysfunction can be used to noninvasively diagnose ACR. Predictive trajectories of the same profile during supervised immunosuppression minimization diagnosed rejection up to 40 days prior to clinical expression. The rejection‐associated miRNAs in sera appear to be ectopically expressed liver and specific immune cell miRNAs that are biologically related, and the consequences of immune‐mediated damage to the allograft. (Hepatology 2017;65:269‐280).